The role of human resources development in achieving sustainable development and ways to integrate them with the economic institution “study of the case of EL Hodna Milk in M’sila -Algeria” - Guerrouat, Younes; Slah, Mohammed; Benouaret, Hadjila (Dirassat Journal Economic Issue, 2021)
The optimal use of the available and anticipated human element and the reliance on the efficiency, capabilities and bounties of this human element and its enthusiasm for work ensure the efficiency and success of the organization in achieving its objectives, so management scientists were interested in developing principles and foundations that help to make the most of each individual in the organization through human resources management and development, these foundations start from planning, selection, training, incentives and evaluation, and are not separate from each other, but are integrated with each other as a system that seeks to reach the efficient performance of human resources and human resources. Then the organization as a whole within the framework of achieving sustainable development.